Is Hogarth's 'Line of Beauty' really the most beautiful? An empirical answer after more than 250 years. (March 2022) - Hübner, Ronald; Ufken, Emily
Since the Renaissance, different line types have been distinguished by artists and art theorists. However, it took another hundreds of years until the British artist William Hogarth attributed different degrees of beauty to them. Particularly, in his book "The Analysis of Beauty" (1753) he depicted seven waving lines, declared line number 4 as the most beautiful, and called it the "line of beauty". Until today, the line of beauty has a persistently strong influence in many areas such as landscape art and design, calligraphy, furniture design, architecture, dance, etc. It is astonishing that Hogarth's assumptions have never been empirically tested. Therefore, we asked participants to rate Hogarth's lines by their beauty. As a result, line number 4 was indeed the most preferred, although number 5 was judged similarly. An analysis revealed that curvature was nonlinearly related to beauty and explains more than 90% of the variance in the mean aesthetic judgments.